2009
DOI: 10.1002/jmv.21555
|View full text |Cite
|
Sign up to set email alerts
|

Detection of all four human metapneumovirus subtypes in nasopharyngeal specimens from children with respiratory disease in Uberlândia, Brazil

Abstract: The human metapneumovirus (hMPV) is a pathogen of the respiratory tract identified first in the Netherlands in 2001 and since then it has been detected worldwide. The purpose of this study was to identify and characterize hMPV in samples collected from children <5 years presenting with acute respiratory disease (ARD) seen at a public hospital in Uberlândia, in Southeastern Brazil. One hundred fourteen nasopharyngeal aspirates (NPAs) samples that were negative for the presence of nine other respiratory viruses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…Brazil has already been demonstrated 3,5,8,31,35 . No vaccine or antiviral therapy is currently available for prevention or treatment of HMPV infection.…”
Section: The Burden Of Hmpv Infection Inmentioning
confidence: 99%
“…Brazil has already been demonstrated 3,5,8,31,35 . No vaccine or antiviral therapy is currently available for prevention or treatment of HMPV infection.…”
Section: The Burden Of Hmpv Infection Inmentioning
confidence: 99%
“…For instance, while lineage A1 circulated extensively in humans from 1982 to 2003 (233, 253), it has rarely been detected since 2004. In numerous other studies, it has been shown that the predominant circulating strains may vary by year and that predominant strains may be replaced, on average, every 1 to 3 years (2,9,40,44,70,118,140,146,152,154,166,177,185,188,242).…”
Section: Molecular Epidemiology and Virus Evolutionmentioning
confidence: 99%
“…Briefly, RSV A and B and FLU A and B were detected using multiplex two-step PCR reactions with previously described primers and conditions (Stockton et al 1998). Human metapneumovirus (hMPV) was detected using a protocol that was previously described by our group (Carneiro et al 2009). Finally, PIV 1-3 were detected using the primers and conditions published by Echevarría et al (1998).…”
Section: Patients and Clinical Specimensmentioning
confidence: 99%
“…RSV A and B and FLU A and B (Stockton et al 1998) were the first viruses tested for, followed by hMPV (Carneiro et al 2009) and PIV 1-3 (Echevarría et al 1998). This order was chosen according to clinical relevance of co-infections in children as determined by the literature (Aberle et al 2005, Calvo et al 2008, Cilla et al 2008) and because of the circulation rate of the most common viruses in the region (Costa et al 2006).…”
Section: Patients and Clinical Specimensmentioning
confidence: 99%